1991
DOI: 10.1161/01.cir.83.4.1333
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of DuP 753, a specific angiotensin II receptor antagonist, to normal male volunteers. Inhibition of pressor response to exogenous angiotensin I and II.

Abstract: DuP 753 appears to be a well-tolerated, orally active, potent, and long-lasting antagonist of angiotensin II in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(110 citation statements)
references
References 32 publications
7
101
0
Order By: Relevance
“…Thus, the long duration of the antihypertensive effect of valsartan, observed in renal hypertensive rats, appears to be due to a blockade of the AT,-receptor. Long lasting inhibition of AII-induced pressor responses have also been reported with losartan in normal male volunteers (Christen et al, 1991).…”
Section: -mentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, the long duration of the antihypertensive effect of valsartan, observed in renal hypertensive rats, appears to be due to a blockade of the AT,-receptor. Long lasting inhibition of AII-induced pressor responses have also been reported with losartan in normal male volunteers (Christen et al, 1991).…”
Section: -mentioning
confidence: 74%
“…This compound is an efficacious antihypertensive agent in animals (Wong et al, 1990a,d) and is also active in man (Christen et al, 1991). The blood pressure-lowering effect of losartan in rats, however, depends partly on its conversion to the active, hepatically generated carboxylic acid metabolite, EXP3174, which is about 20 times more potent than the parent compound as an AT,-receptor antagonist (Wong et al, 1990c;Timmermans et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinical pharmacology studies have confirmed that losartan blocks the Ang II receptor. 3 Clinical trials have demonstrated that losartan potassium given alone lowers blood pressure (BP) and is well tolerated in longterm trials in patients with essential hypertension. 4 Despite the efficacy of losartan potassium or other monotherapy agents such as hydrochlorothiazide (HCTZ), some patients with more resistant forms of hypertension may require concomitant antihypertensive therapy to control their BP.…”
Section: Introductionmentioning
confidence: 99%
“…Losartan is an angiotensin II receptor antagonist with dilatory effects on arteries and veins. 18 The substance has recently been approved for the treatment of arterial hypertension. As yet, its influence on portal hypertension has not been investigated.…”
mentioning
confidence: 99%